Navigating young fatherhood: experiences and coping strategies of unmarried fathers raising children born out of wedlock - Oratile Sibongile Mafora; Tsholofelo Shophi; Frans Koketso Matlakala (Discover Mental Health)
Abstract Background Young fatherhood is challenging, especially for young unmarried fathers. With limited research conducted with different cultural groups within South Africa, it has been established that young unmarried fathers face various challenges, such as accessing their children and having conflicts with the child’s mother. However, there is a dearth of literature on studies conducted on the Batswana cultural group regarding challenges faced by young unmarried fathers. Thus, this study explores psychological challenges and coping strategies of unmarried fathers raising children born out of wedlock in Zeerust, South Africa. Methods This study adopted the exploratory design and used face-to-face semi-structured interviews to interview 10 young unmarried fathers raising children born out of wedlock in Zeerust, South Africa. Reflexive thematic data analysis was used to analyse the collected data. Results The study found that the experiences of young unmarried fathers include loss of freedom, emotional distress, and unemployment. However, the coping strategies adopted by these young fathers include both positive and negative coping strategies. These coping strategies include seeking financial stability, financial support, alcohol and substance use, avoidance, coping, and distancing from peer conversation. Conclusions The study concludes that the experiences of young unmarried fathers are determined by their employment status and financial stability. Therefore, the study recommends that social workers should develop interventions targeted at addressing the challenges of young unmarried fathers raising children born out of wedlock and assist young unmarried fathers to develop positive coping strategies.